Antibacterial Evaluation of Alium sativum on Gram-Negative Urinary Tract Bacteria - Garba, L.; Muhammad, R.; Adamu, M.T; Yarma, A.A; Jauro, H. A.; Isa S. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Bacterial pathogens of the Urinary Tract have been prevalent in many settings particularly the community or hospital. The Urinary Tract Infections may be symptomless or symptomatic and classified as bladder infection (cystitis), kidney infection (pyelonephritis), and urine infection (bacteriuria). The emergence of antibiotic resistance particularly among bacterial pathogens has necessitated the need to search medicinal plants for bioactive compounds as possible alternative source of potent antimicrobial agents. Garlic is a plant that is well-known as hardy perennial member of onion family. Previous reports have confirmed the antimicrobial activity of Garlic extracts, however, assessment of garlic in vitro inhibitory activity appears to be the first in the study area to the best of our knowledge. One hundred (100) mid-stream urine samples were collected from pregnant women in Liji primary healthcare and brought to Microbiology laboratory of Gombe State University for analysis. The samples were cultured on Nutrient and MacConkey agar plates prepared according manufacturers recommendation. The plates were incubated at 37 oC for 24 hours. After incubation, the bacterial colonies were identified based on cultural characteristics, Gram staining and biochemical tests. Garlic extract was prepared in methanol using percolation method. The extract recovered was screened for phytochemicals and tested against the bacteria identified. The results showed that, among the Gram-negative bacteria isolated, Escherichia coli had the highest occurrence of 24(40%) isolates followed by Proteus mirabilis, 15(25%), Klebsiella pneumoniae, 9(15%), Enterobacter aerogenes, 8(13%) and Citrobacter freundii, 4(7%) isolates. Various concentrations (50-400 mg/mL) of garlic methanolic extract tested showed that E. aerogenes was the most sensitive bacterium while the least sensitive organism was E. coli. The phytochemicals detected include saponins, tannins, flavonoid, and steroid. In conclusion, the garlic extract was found to be effective against all the Gram-negative bacteria tested.